Oil and gas seepage offshore Georgia (Black Sea) – Geochemical evidences for a paleogene-neogene hydrocarbon source rock. (June 2021) - Pape, Thomas; Blumenberg, Martin; Reitz, Anja; Scheeder, Georg; Schmidt, Mark; Haeckel, Matthias; Blinova, Valentina N.; Ivanov, Michael K.; Sahling, Heiko; Wallmann, Klaus; Bohrmann, Gerhard
Abstract: Numerous hydrocarbon seep sites at the continental shelf, slope, and in the deep water basin are known to feed the Black Sea water reservoir of dissolved methane. In this study, we identified the likely sources of gas and oil that are emitted at four sites located on the continental slope offshore Georgia in the Eastern Black Sea at 830 to 1, 140 m water depth – an area with gas seepage only (Batumi seep area) and three areas of coupled gas and oil seepage (Iberia Mound, Colkheti Seep, and Pechori Mound). The geochemistry of bulk parameters, organic fractions and individual hydrocarbon biomarkers in near-surface sediments and of gas/oil expelled from the seafloor was analyzed and jointly interpreted to assign most likely hydrocarbon source rocks in the studied region. Presence of oleanane in shallow oil-impregnated sediments and oil slicks attests that the source rock at all sites is younger than Mid Cretaceous in age. We conclude that hydrocarbons ascending at all the four seepage areas originate from the Eocene Kuma Formation and/or the Oligocene–Lower Miocene Maikop Group, which are considered the principal hydrocarbon sources in the Eastern Black Sea region. Distributions of crude oil biomarkers in shallow sediments suggests moderate to heavy biodegradation. C1 /C2+ ratios (10–4, 163) along with stable C and H isotopic ratios (δ 13 C–CH4 ‒46.3 to −53.1.3‰ V-PDB; δ 2 H–CH4 ‒159 to −178‰ V-SMOW) indicate gas mixtures of oil-associated thermogenic and secondary microbial light hydrocarbons that are discharged from the four seep sites. Light hydrocarbons discharged at the Batumi Seep area are characterized by significant enrichments of methane, but have almost similar δ 13 C–CH4 values if compared to the other study sites. Such methane enrichments likely result from a comparably higher degree of petroleum degradation and associated formation of secondary microbial methane. Highlights: Four seafloor hydrocarbon emissions in the Eastern Black Sea were investigated. Eocene and/or Oligocene-Miocene Formations are most likely sources for oil and gas. Mixed secondary microbial and oil-associated thermogenic hydrocarbons at all sites. Site-specific light hydrocarbon compositions result from different mixing ratios.